Nonstationary Transfer of Components of an Isotopic Mixture as a Result of the Change in Cascade Flows; Journal of Engineering Physics and Thermophysics; Vol. 92, iss. 4 - Orlov A. A. Aleksey Alekseevich (2019, 2019)
Title screen